Optimization of the Factors Influencing Biodegradation and Thermal Stability of Banana Pseudo Stem Fibers in Nigeria. Issue 1 (31st December 2023) - Oyewo, Abideen Temitayo; Oluwole, Oluleke Olugbemiga; Ajide, Olusegun Olufemi; Omoniyi, Temidayo Emmanuel; Kim, Hyunjin; Choi, Yong Jun; Park, Young-Kwon; Hussain, Murid
ABSTRACT: Lignocellulosic fibers, one of natural biopolymers, are derived from abundant banana pseudo stem (BPS) agricultural waste in different parts of Nigeria. In this study, the lignocellulosic fibers of three common banana cultivars, agbagba, paranta, and omini, were investigated to determine their chemical composition and mechanical properties. Furthermore, the experimental investigations were correlated with the corresponding Taguchi L9 orthogonal array design under three factors – fiber treatment, diameter, and cultivar type – to find the optimal factors that are pertinent to the desired biodegradation and thermal stability of the fibers. The optimization results indicated that the fiber treatment followed by diameter and the cultivar type was the most influential of the responses, respectively. However, increased cellulosic content led to higher tensile strength and modulus, while higher lignin corresponded to higher elasticity. Meanwhile, the predictions of the biodegradation and thermal stability derived from the Taguchi design via S/N ratio ANOVA and regression modeling correlated adequately with the corresponding experimental observations. Ultimately, the fibers with optimum factors were T3D1C1 and T3D1C3, where T3, D1, C1, and C3 denote that the associated fiber was treated with acetic acid, had a diameter of 60.77 µm, and belong to the cultivar type of agbagba and omini, respectively.